A STUDY ON INFRASTRUCTURE AND ORGANIZATIONAL LEARNING: RETHINKING KNOWLEDGE PERFORMANCE PERSPECTIVE - K. Singh, Pooja; Kumar, Manoj (PEOPLE: International Journal of Social Sciences, 2017)
This paper aims to present an integrated outlook of knowledge performance by reviewing the linkage between knowledge management (KM) infrastructure and organizational learning dimensions. The study endorses infrastructure capabilities i.e. culture, structure, technology and human resource to influence learning which subsequently leads to enhance knowledge performance within organizational context. A systematic review has been applied to assess KM literature including prior conceptual and research studies that help to substantiate the linkages among KM infrastructure, organizational learning and knowledge performance. The proposed conceptual model provides insights for managers and strategists to analyze the role of KM infrastructure in improving learning practices and knowledge performance. Furthermore, this study emphasizes on enabling learning processes and knowledge infrastructure dimensions, particularly mentioned by Lee and Choi (2003). In spite of various researches in KM there is still a need to review the linkages among the key elements which may affect knowledge performance. This paper contributes to the KM literature by adjoining KM infrastructure to organizational learning and visualizes the integrative effect that may enhance knowledge performance. Study limitations and future scope of the study has also been discussed in the later section.